Modern numerical methods for high-fidelity simulation of geohazards - (:unkn) unknown (My University, 2026)
Геологічні небезпеки, такі як гірські лавини, зсуви і селеві потоки, зазвичай визнаються повільними або швидкими гравітаційними процесами, які відбуваються в гірських регіонах, таких як Альпи в Європі, Гімалаї в Азії, Скелясті гори в Північній Америці і Снігові гори в Австралії, та характеризуються потенційними небезпеками. З розвитком комп'ютерних наук чисельне моделювання геологічних небезпек стало вирішальним у сучасній геомеханіці та геотехнічній інженерії. Фрагментарність поточних досліджень в рамках локальних національних проектів часто не дає комплексного розуміння механізмів еволюції. Ця прогалина призводить до того, що сучасні чисельні методи високоточного моделювання залишаються "сірою зоною", обмежуючи доступ до них як для наукових дослідників, так і для інженерів практиків. MONUGEO об'єднує взаємодоповнюючий досвід членів нашого консорціуму для кращого розуміння процесів формування, перебігу та впливу небезпечних геолоігчних процесів (та/або взаємодії із захисними перешкодами) і, в свою чергу, для створення іноваційних чисельних інструментів для високоточних прогнозів. Наш міжнародний міждисциплінарний консорціум також надаватиме перевагу комплексному дослідницькому підходу, що включає лабораторні експерименти, фізичне центрифужне модлеювання та регіональні геологічні дослідження. Ця інтегрована методологія слугуватиме для перевірки розроблених нами обчислювальних парадигм і чисельного інструментарію, а також для застосування їх до реалістичних сценаріїв.

Geohazards, such as rock avalanches, landslides and debris flows, are commonly recoganized as the slow-to-rapid gravitationally driven processes that typically occur in mountain regions, such as Alps in Europe, Himalaya in Asia, Rocky in North Americas and Snowy in Australia, possessing potential hazards societies. With the advancement of computer science, numerical simulations of geohazards have become crucial in the modern geomechanics and geotechnical engineering. The fragmentation of current research into local national projects often falls short in comprehensive understanding of the evolution mechanisms. This gap results in a grey area in modern numerical methods for high-fidelity simulations, limiting accessibility for both scientific researchers and engineering practitioners. MONUGEO brings together the complementary expertise of our consortium members to develop a better understanding of triggering initiation, run-out and deposition (and/or interaction with protective obstacles) processes, and in turn to produce the ground breaking numerical tools for the high-fidelity predictions. Our international and interdisciplinary consortium will also prefer to an integrated research approach, involving laboratory experiments, scaled centrifuge physics modelling tests, and region-scale application with geological survey. This integrated methodology will serve to validate our developed computing paradigms and numerical toolbox, and to apply them to realistic scenario.
Сучасні чисельні методи високоточного моделювання геонебезпек
Keywords: Civil engineering; maritime/hydraulic engineering; geotechnics; waste treatment; Computational engineering and computer aided design; Environmental engineering and geotechnics; Mountain geohazards; Rock avalanches; Landslides; Modern numerical methods; Multiscale simulations